Socioeconomic status and fertility intentions among Chinese women with one child. (2nd January 2016) - Zheng, Yumei; Yuan, Jingqin; Xu, Tan; Chen, Mei; Liang, Hui; Connor, Donovan; Gao, Yongqing; Sun, Wenjie; Shankar, Nivedita; Lu, Chuanwen; Jiang, Yan
Abstract: There has been a lack of socioeconomic status (SES) disparity analysis on women in China with only one child, the family planning target population. In 2008, the National Research Institute for Family Planning of China conducted a study investigating the relationship between SES and fertility intentions among 17, 093 women in China who already had one child. A questionnaire was used to collect information on SES and fertility intentions, and logistic regression models were used to estimate the odds ratios and 95% CIs of fertility intentions according to SES. Compared with female farmers, women in other occupations intended to have fewer children ( p  < 0.05). Additionally, compared with women with low educational level (illiterate/primary), women with secondary and postsecondary education intended to have fewer children ( p  < 0.05) (OR = 0.70; 95% CI: 0.61–0.81 and OR = 0.56; 95% CI 0.47–0.66). A mother's education level was significantly and negatively associated with fertility intentions after adjustment for potential confounders ( p  < 0.05). Among Chinese women who had one child, the women with higher SES (e.g. higher educational level) had lower fertility intentions. There is an SES disparity in the fertility intention among Chinese women who already have one child. China's policy-makers should consider increasing high SES women's fertility intention.